QUALIDADE DE VIDA E ESTADO NUTRICIONAL DE MULHERES SOBREVIVENTES DO CÂNCER DE MAMA EM TERAPIA HORMONAL ADJUVANTE - Flores, Priscila da Trindade (2018)
Breast cancer is the most frequent cause of death associated with cancer in women worldwide and in Brazil. The objective of the present study was to evaluate the epidemiological profile, nutritional status and quality of life of women with breast cancer. The study population was composed of women diagnosed with breast cancer under treatment at the Hospital Universitário de Santa Maria, RS, Brazil. The study was developed in two stages: In step 1, a retrospective cross-sectional study of the Hospital Registry of Cancer, from 2010 to 2013. In stage 2, a cross-sectional study was carried out from January to August 2017. Socio-demographic, anthropometric, lifestyle, quality of life (QoL) data were collected using the Short-Form Health Survey (SF-36) and food frequency questionnaire to assess adherence to lifestyle recommendations from the World Cancer Research Fund (WCRF) and American Institute for Cancer Research (AICR). To evaluate the association between the variables were performed Chi-square test and Kruskal Wallis test. The association between independent variables and outcomes was determined by univariate analysis using crude odds ratios, assuming 95% confidence intervals. Variables with a value of p <0.20 in the univariate analysis will be included in the regression model. Article 1 aimed to evaluate the epidemiological profile and to determine the factors associated with the presence of more than one primary tumor. The sample consisted of 699 women, 88.6% referred to as white. After adjustment, the occurrence of more than one primary tumor was higher in women over 57 years old and exposed to alcohol. In article 2, the objective was to evaluate adherence to the new WCRF / AICR recommendations by Brazilian women in adjuvant hormone therapy and its associated factors. The average adherence score to the WCRF / AICR recommendations was 4.4 points out of a total of 8 points. The highest score is associated with higher adherence, and was correlated with higher schooling. The objective of article 3 was to evaluate the predictive factors associated with QoL of breast cancer survivors in adjuvant hormone therapy with tamoxifen. A total of 143 women were evaluated. Patients who had: external occupation, current smoking, did not practice physical activity, had ≥ 2 associated diseases, presence of ≥ 3 side effects in all domains of quality of life, elevated body mass index (BMI), high waist circumference (WC), high waist-hip circumference (WHR). We can observe in the present articles, the studied population was represented by women of low education, self-declared white in the age group of 50 years. The side effects resulting from the treatment and not practicing physical activity negatively impact the physical and mental quality of life. Most of the women present high anthropometric indexes of BMI, CC and WHR and were associated with worse physical quality of life. The WCRF / AICR recommendations presented low adherence in this population, and were associated with lower schooling.